Eczema and Risk of Cardiovascular Disease: Heightened Awareness Needed - Fujiyoshi, Akira (Journal of Atherosclerosis and Thrombosis, 2019)
[See article vol. 26: 775-782] Recent evidence suggests an association of chronic inflammatory skin diseases, such as psoriasis and atopic dermatitis, with the risk of cardiovascular diseases (CVD). Eczema and dermatitis are frequently used interchangeably, and chronic eczema (chronic dermatitis) is a common skin disorder worldwide. Among the subtypes of chronic eczema, the association of psoriasis with CVD has been reported to be strong. However, the association of atopic dermatitis (atopic eczema) with CVD remains unestablished. Atopic dermatitis is the most common type of eczema and traditionally considered a disease that occurs during childhood; however, approximately 50% of these childhood cases can extend into adulthood, evolving into a life-long condition. The estimated prevalence of adults with eczema or atopic dermatitis is 6.9% and 10.2% in Japan and the United States, respectively. Given such a high prevalence, even a small increase in the risk of CVD would be important from a public health perspective. Nonetheless, only a limited number of population-based studies have examined a longitudinal association of chronic dermatitis with CVD in adults.